Effect of Auxin on Rooting Cuttings of Skimmia laureola Hook. - Badola, K. C.; Goel, C. L. (Indian Forester)
Rooting trials using hardwood cuttings of Skimmia laureola were conducted at 1-month intervals with and without auxin treatment. It was observed that per cent callusing and rooting was higher in July and August, lower in Sepember and cuttings failed to root in october. The results indicate that S. laureola can be vegetatively propagated by rooting cuttings, and that August is the best month and 150 ppm IAA optimum treatment for obtaining best results.